Enhancing Sweat Rate Using a Novel Device for the Treatment of Congestion in Heart Failure. (2nd November 2022) - Aronson, Doron; Nitzan, Yaacov; Petcherski, Sirouch; Bravo, Evgeny; Habib, Manhal; Burkhoff, Daniel; Abraham, William T.
Abstract : Background: Current treatment of fluid retention in heart failure relies primarily on diuretics. However, adequate decongestion is not achieved in many patients. We aimed to study the feasibility and short-term performance of a novel approach to remove fluids and sodium directly from the interstitial compartment by enhancing sweat rate. Methods: We used a device designed to enhance fluid and salt loss via the eccrine sweat glands. Skin temperature in the lower body was increased from 35 °C to 38 °C, where the slope of the relationship between temperature and sweat production is linear. The sweat evaporates instantaneously, thus avoiding the awareness of perspiration. The primary efficacy endpoint was the ability to increase skin temperature to the desired range. A secondary efficacy endpoint was a clinically meaningful hourly sweat output, defined as ≥150 mL/h. The primary safety endpoint was any procedure-related adverse events. Results: We studied 6 normal subjects and 18 patients with congestion. Participants underwent 3 treatment sessions of up to 4 hours. Skin temperature increased to a median of 37.5 °C (interquartile range, 37.1–37.9 °C) with the median core temperature increasing by 0.2 °C (interquartile range, 0.1–0.3 °C). The median hourly weight loss during treatment was 215 g/h (interquartile range, 165–285; range, 100–344 g/h). In 80% of treatment procedures, the average sweat rate was ≥150 mL/h. There were no significant changes in hemodynamic variables or renal function and no procedure-related adverse events. Conclusions: Enhancing sweat rate was safe and resulted in a clinically meaningful fluid removal and weight loss. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT04578353.